(3efThQ fUQ GHf aJhMs - (3fUQ Hf aJhMs
(3ChdgG (B:s
(3hUdJ ecGJHGJ GdTjN GdNjQ GdOjf GWGd Gddg ai Seh efRdJg HbGg hGMSf Yf MejO WGYJg hGLJgGOg LRGg s
(3BNQgG (B:s
(3hYQage Cf gPg GdecGJHg ef bHd hUhd cJGHc djYQahG efg hdi GdReGf hjJCOHhG HeG gh BJ hHeG bO cGf JeJ Hefg hdi GdMb s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B25s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3eUOQ GbJfGA GdCUd (B:s
(3GdLGeYI GdCeQjcjI ai HjQhJ s
Keywords: (3abg GdePGgH GdCNQis